Fracture toughness mode I of glass fibers improved soil. (2022) - Rizvi, Zarghaam; Amin, Arshi; Arp, Joan Chetam Christine; Wuttke, Frank
Abstract: Cohesive soil at low saturation starts to behave like a quasi-brittle material and fails predominately under fracture modes defined by linear elastic fracture mechanics. The fracture toughness of soils is the ability to resist crack initiation and propagation and therefore becomes a desirable property for computation of safe design limits of lifeline structures such as pipelines, bridges and dams. In this paper, we present fracture toughness mode I results of cohesive soil with a three-point bending at different levels of water content. The maximum toughness value is reported at 18% water content. Furthermore, glass fibers with 0.01–0.1% weight of the soil are used to strengthen the soil, and the measurements are performed showing a significant change in the fracture toughness. The results also indicate stiffness enhancement of the treated soil as the glass fibers behave like a minute reinforcement in the soil mass shown with SEM images. However, fracture toughness and the behavior of the soil fiber mixture start to show degradation with additional glass fiber and water content. The maximum KIC value for 17 and 18% moisture content is found to be with 0.01% glass fiber.